Two-point problem for systems of differential equations with partial - Клюс, І.С. (Proceedings of National Aviation University (archive), 2009)
The correctness of a problem with local two–point conditions on temporary variable and conditions of periodicity on spatial coordinates for the triangle system of partial differential equations. The conditions of existence and uniqueness of the solution of a problem are established. The metric theorem of an estimation from below of small denominators of a problem is proved.